2015
DOI: 10.2337/db15-0941
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric Fat Lipolysis Mediates Obesity-Associated Hepatic Steatosis and Insulin Resistance

Abstract: Hepatic steatosis and insulin resistance are among the most prevalent metabolic disorders and are tightly associated with obesity and type 2 diabetes. However, the underlying mechanisms linking obesity to hepatic lipid accumulation and insulin resistance are incompletely understood. Glycoprotein 130 (gp130) is the common signal transducer of all interleukin 6 (IL-6) cytokines. We provide evidence that gp130-mediated adipose tissue lipolysis promotes hepatic steatosis and insulin resistance. In obese mice, adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
68
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 57 publications
5
68
0
1
Order By: Relevance
“…No studies have measured overfeeding effects on lipolysis in humans. High saturated fat-feeding in mice stimulates lipolysis via inflammatory mediators (6). In keeping with such data, we found upregulation of multiple inflammationrelated pathways in the adipose tissue transcriptome.…”
Section: Pathways Of Ihtgsupporting
confidence: 87%
See 1 more Smart Citation
“…No studies have measured overfeeding effects on lipolysis in humans. High saturated fat-feeding in mice stimulates lipolysis via inflammatory mediators (6). In keeping with such data, we found upregulation of multiple inflammationrelated pathways in the adipose tissue transcriptome.…”
Section: Pathways Of Ihtgsupporting
confidence: 87%
“…Excess sugar intakes increase DNL and IHTG content in humans (5). In mice, a high-fat diet increases adipose tissue lipolysis (6). The pathway by which IHTGs are synthesized in response to overconsuming fat has not been studied in humans.…”
mentioning
confidence: 99%
“…Visceral fat cells in vitro have increased lipid synthesis and lipolysis compared to abdominal subcutaneous adipocytes, findings that have been corroborated in vivo in short-term experimental settings678. As vWAT is drained by the portal vein, increased levels of portal fatty acids may cause liver-associated metabolic complications, such as hepatic steatosis and/or hepatic insulin resistance, in the overweight and obese states9101112.…”
mentioning
confidence: 89%
“…8,9 Rytka et al found that mice receiving a portal drained fat transplant, similar to MAT, had worse hepatic insulin resistance compared to mice receiving vena cava drained fat. 10 Mesenteric adipose tissue inflammation contributes to NAFLD, but what promotes MAT inflammation is still not clear. 10 Mesenteric adipose tissue inflammation contributes to NAFLD, but what promotes MAT inflammation is still not clear.…”
Section: Introductionmentioning
confidence: 99%